Rural Education: A Gravel Road in a World of Highways - Rugama López, Bryan (2017)
This essay aims to provide some insight into some of the situations that rural education in Costa Rica has to face in terms of the educational practices developed in it since these are different from the ones found in some educational institutions of the metropolitan area. Rural areas demand a better education and better social and educational policies.